Adaptação de um modelo de avaliação de desempenho para produtos: o caso de isolantes térmicos desenvolvidos para aplicação nas subestações elétricas do nordeste brasileiro. - Resende, Sheyla Rodrigues de (2011)
This research aims to tailor a system of performance evaluation to assist the choice of a new product that will be applied as thermal insulation, electrical substations. The performance evaluation systems can be considered as a set of metrics and processes used to obtain it, in order to quantify the efficiency and effectiveness of a system, enabling a systemic analysis of the object of evaluation.Therefore, we chose to identify and match an existing model from the literature to apply it in the selection of new products. The electrical substation is where the products developed will be applied. Therefore, it was considered essential to know in depth all the requirements necessary for the proper design, construction and operation of substations, checking criteria or restrictions which could influence the choice of product to be applied. Thermal comfort of buildings is the main functionality of the product developed, immediately there was a need to identify which characteristics of the materials have more influence in this regard and indicators which could not fail to be considered. The proposed methodology followed a pre-defined, in which selected the quantum model as a basis to describe a performance evaluation model capable of quantifying the performance of products. The analysis showed that the thermal insulation of EVA performed better in quality and cost categories, with only a lower performance in the category of measurement time. Another relevant security concerns, as this insulation achieved a performance inferior to the others, but enough for use in electrical substations.